2021
DOI: 10.1186/s12870-021-02990-y
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification, evolutionary estimation and functional characterization of two cotton CKI gene types

Abstract: Background Casein kinase I (CKI) is a kind of serine/threonine protein kinase highly conserved in plants and animals. Although molecular function of individual member of CKI family has been investigated in Arabidopsis, little is known about their evolution and functions in Gossypium. Results In this study, five cotton species were applied to study CKI gene family in cotton, twenty-two species were applied to trace the origin and divergence of CKI g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…CKI gene in tetraploid G. littoralis was significantly up-regulated. Previous study in cotton had found that CKI gene was underwent amplification with cotton tetraploid event and it was involved in the response to light signals [ 36 ]. In Arabidopsis , the Casein kinase 1 family regulates PRR5 and TOC1 in the circadian clock, impacting crucial plant processes like photosynthesis, cell elongation, stress responses, and flowering, with potential effects on biomass or yield [ 37 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…CKI gene in tetraploid G. littoralis was significantly up-regulated. Previous study in cotton had found that CKI gene was underwent amplification with cotton tetraploid event and it was involved in the response to light signals [ 36 ]. In Arabidopsis , the Casein kinase 1 family regulates PRR5 and TOC1 in the circadian clock, impacting crucial plant processes like photosynthesis, cell elongation, stress responses, and flowering, with potential effects on biomass or yield [ 37 40 ].…”
Section: Discussionmentioning
confidence: 99%